2016
DOI: 10.3390/s16010103
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Reduced Graphene Oxide and Graphite Oxide in the Aspect of Their Possible Application in Gas Sensors

Abstract: The paper presents the results of investigations on resistance structures based on graphite oxide (GRO) and graphene oxide (rGO). The subject matter of the investigations was thaw the sensitivity of the tested structures was affected by hydrogen, nitrogen dioxide and carbon dioxide. The experiments were performed at a temperature range from 30 °C to 150 °C in two carrier gases: nitrogen and synthetic air. The measurements were also aimed at characterization of the graphite oxide and graphene oxide. In our meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
116
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(133 citation statements)
references
References 41 publications
15
116
0
2
Order By: Relevance
“…Spectrum 5(a) reveal two characteristic bands at 1347 cm −1 (D band) and 1587 cm −1 (G band) for GO which are shifted to 1324 cm −1 (D band) and 1573 cm −1 (G band) after reduction. Relative intensity ratio I D /I G increases from 1.80 to 1.84 after reduction due to the increase in defects . Similar result was observed from spectrum 5(b) that I D /I G intensity ratio increase from 3.34 to3.52 (Two prominent bands were observed at 1312 cm −1 (D band) and 1585 cm −1 (G band) which shift to 1309 cm −1 (D band) and 1578 cm −1 (G band) for rGO).…”
Section: Raman Spectroscopy Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…Spectrum 5(a) reveal two characteristic bands at 1347 cm −1 (D band) and 1587 cm −1 (G band) for GO which are shifted to 1324 cm −1 (D band) and 1573 cm −1 (G band) after reduction. Relative intensity ratio I D /I G increases from 1.80 to 1.84 after reduction due to the increase in defects . Similar result was observed from spectrum 5(b) that I D /I G intensity ratio increase from 3.34 to3.52 (Two prominent bands were observed at 1312 cm −1 (D band) and 1585 cm −1 (G band) which shift to 1309 cm −1 (D band) and 1578 cm −1 (G band) for rGO).…”
Section: Raman Spectroscopy Analysissupporting
confidence: 83%
“…Figure (b) shows highly wrinkled structure of rGO in comparison to GO. It has been reported that highly wrinkled reduced graphene oxide nanosheets are more sensitive and show better recovery ability . From Figure (a) and (b), it is clear that surface of the sample gets corrugated on reduction from GO to rGO.…”
Section: Raman Spectroscopy Analysismentioning
confidence: 81%
“…The peak located at ∼289.7 eV could be assigned to satellite peak corresponding to the π‐π* transition in the aromatic systems (∼290.4 eV). These values matched well with those reported by Drewniak et al , Briggs et al and Stankovich et al .…”
Section: Resultssupporting
confidence: 93%
“…The nanosheets of GO are observable in Figure (a), which has a crumpled and wrinkled structure. Restacking of these nanosheets is inevitable, and the entanglement of them with each other reduces their surface area . The image of CuFeO 2 (Figure b) reveals the aggregation of these nanoparticles and the size of them was estimated to be 70–90 nm, which is in accordance with XRD results.…”
Section: Resultssupporting
confidence: 80%